The Effect Of A Combination Of Speos (Endorphine Massage Stimulation, Oxytocin Massage And Suggestion) On The Success Of The Let Down Reflex And The Production Of The Mother's Milk Production Post Sectio Caesarea At Dr. Hospital. H. Slamet Martodirdjo Pam - Noviandry R, Hilmah; C, Elisa; Setya F, Cucun; R, Sylvina (CV. Inara, 2023)
Exclusive breastfeeding has a major impact on a baby's growth and development, as breast milk contains immune system proteins and high levels of bactericides, and breastfeeding can reduce the risk of a baby dying. At the 65th World Health Assembly, member countries of the World Health Organisation (WHO) set a target for at least 50% of babies under six months to be exclusively breastfed by 2025. With massage stimulation that stimulates the release of endorphins and oxytocin, as well as suggestions from the SPEOS method, it will create feelings of calm and strong confidence in the mother, which will influence the let-down reflex. The combination of endorphin massage, oxytocin and suggestive massage can lead to a smooth flow of breast milk, which will help the mother to meet the nutritional needs of the baby for its growth and development. The aim of this research is to determine the success of the let down reflex and the smooth production of breast milk (ASI) after a combination of endorphin massage, oxytocin and suggestive massage intervention. This research uses a post-test only control design, which is a type of true experimental design methodology. The study population consisted of thirty mothers after caesarean section on the first and second day in the delivery and postpartum room of Dr. RSUD. H. Slamet Martodirdjo Pamekasan. The sampling technique used in this study was purposive quota sampling. Data analysis in this study used bivariate and multivariate analysis, namely T-test. In this research design, there were 2 groups, namely the intervention group, namely post caesarean mothers who were given SPEOS intervention and the control group, namely post caesarean mothers who were not given SPEOS intervention. The results of statistical tests using a paired sample t-test on the control group showed results of sig-2 tailed = 1,000 > 0.05, meaning that there was no difference in the let down reflex and smoothness of breast milk production in the control group. The results of statistical tests using a paired sample t-test on the treatment group showed results of sig-2 tailed = 0.000 < 0.05, meaning that there was a difference in the let down reflex and smoothness of breast milk production in the treatment group after receiving the SPEOS intervention, so the hypothesis was accepted, meaning that there was a combination effect of SPEOS (stimulation). endorphin massage, oxytocin and suggestive massage) on the success of the let down reflex and the smoothness of the mother's breast milk production after caesarean section at RSUD Dr H. Slamet Martodirdjo Pamekasan in 2023.